Strategi Pemasaran UMKM Pempek Noy dalam Meningkatkan Daya Saing di Era Digital - Yosi Fahdillah; Mira Gustiana Pangestu; Wahya Iffa Lubis (Haka Vyza Media, 2026)
Times This study aims to explore the marketing strategies implemented by the Pempek Noy MSME in enhancing its competitiveness in the digital era. Using a qualitative approach, this research focuses on understanding how the business adapts to digital transformation through various marketing practices. Data were collected through in-depth interviews, direct observation, and documentation involving the business owner and related stakeholders. The findings reveal that Pempek Noy applies a combination of conventional and digital marketing strategies, including the utilization of social media platforms, online marketplaces, and content-based promotion to reach a wider customer base. In addition, entrepreneurial characteristics such as innovation, risk-taking, and adaptability play a crucial role in supporting marketing effectiveness. The study also highlights that maintaining product quality, strengthening customer relationships, and leveraging digital platforms are key factors in sustaining competitive advantage. This research contributes to the understanding of how MSMEs can optimize marketing strategies in the digital era and provides practical insights for small businesses in the culinary sector to improve their competitiveness.